Maven essentials get started with the essentials of Apache Maven and get your build automation system up and running quickly - Siriwardena, Prabath (Packt Publishing, 2015)
Get started with the essentials of Apache Maven and get your build automation system up and running quickly About This Book Explore the essentials of Apache Maven essentials to arm yourself with all the ingredients needed to develop a comprehensive build automation system Identify the extension points in Apache Maven and learn more about them in-depth Improve developer productivity by optimizing the build process with best practices in Maven using this compact guide Who This Book Is For The book is ideal for for experienced developers who are already familiar with build automation, but want to learn how to use Maven and apply its concepts to the most difficult scenarios in build automation. What You Will Learn Comprehend the key concepts in Apache Maven Build your own custom plugins and get to know how Maven extension points are used Troubleshoot build issues with greater confidence Optimize Maven's configuration settings Write custom lifecycles and extensions Get hands-on and create a Maven assembly Explore the best practices to design a build system that improves developer productivity In Detail Maven is the #1 build tool used by developers and it has been around for more than a decade. Maven stands out among other build tools due to its extremely extensible architecture, which is built on of the concept of convention over configuration. It's widely used by many open source Java projects under Apache Software Foundation, Sourceforge, Google Code, and more. Maven Essentials is a fast-paced guide to show you the key concepts in Maven and build automation. We get started by introducing you to Maven and exploring its core concepts and architecture. Next, you will learn about and write a Project Object Model (POM) while creating your own Maven project. You will also find out how to create custom archetypes and plugins to establish the most common goals in build automation. After this, you'll get to know how to design the build to prevent any maintenance nightmares, with proper dependency management. We then explore Maven build lifecycles and Maven assemblies. Finally, you will discover how to apply the best practices when designing a build system to improve developer productivity. Style and approach This book is a practical and compact guide that will show you how to use Apache Maven in an optimal way to address enterprise build requirements. It provides technical guidance to get you started with Maven and build automation.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed December 29, 2015)
Keywords: Computer software -- Development; COMPUTERS; Software Development & Engineering; Tools; Computer software; Development